The longitudinal association of common susceptibility variants for type 2 diabetes and obesity with fasting glucose level and BMI - Beilby John P; Warrington Nicole M; Webster Rebecca J; Frayling Timothy M; Palmer Lyle J (BMC, 2010)
Abstract Background Variation in the effects of genetic variants on physiological traits over time or with age may alter the trajectories of these traits. However, few studies have investigated this possibility for variants associated with type 2 diabetes or obesity, and these show little consensus. We aimed to characterise the possible longitudinal associations of common diabetes-susceptibility variants in the KCNJ11, PPARG, TCF7L2, IGF2BP2, CDKAL1, SLC30A8 and HHEX gene loci, with fasting glucose level; and of an obesity-associated variant in the FTO gene, with body mass index (BMI). Methods The study analysed data from the Busselton Health Study (n = 4,554). Cross-sectional association analyses included family data and used the total association test. Longitudinal association analyses of unrelated participant data (n = 2,864) used linear mixed-effects models. Results In cross-sectional analyses, we observed associations of the T allele at the IGF2BP2 single nucleotide polymorphism (SNP) rs4402960 with raised fasting glucose (p = 0.045), and the A allele at the FTO SNP rs9939609 with raised BMI (p = 0.003). Longitudinal analyses showed no significant associations between SNPs and changes in fasting glucose or BMI in the same individuals, either over mean follow-up times of 18.7 and 21.8 years respectively, or with age during adulthood. Conclusions There was no indication that the effects of common type 2 diabetes variants on fasting glucose varied with age during adulthood or over time.